2013
DOI: 10.1007/s00405-012-2296-9
|View full text |Cite
|
Sign up to set email alerts
|

The use of bone cement for ossicular chain defects

Abstract: Bone cement is a good and cheap option for some ossicular chain problems such as incudostapedial re-bridging. The purpose of this retrospective study is to evaluate the audiologic results after reconstruction of three different types of ossicular chain defects, using bone cement. Group 1 consists of 42 patients who underwent an ossiculoplasty using bone cement between the damaged long process of the incus and an intact stapes superstructure. Group 2 consists of 46 patients in which incus interposition between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 19 publications
0
24
0
3
Order By: Relevance
“…In cases where lenticular process has been damaged or inxus luxated appropriate reconstruction in necessary. Several possible techniques are possible including bone cement bridging, incus interposition or joint prosthesis use [15]. …”
Section: Discussionmentioning
confidence: 99%
“…In cases where lenticular process has been damaged or inxus luxated appropriate reconstruction in necessary. Several possible techniques are possible including bone cement bridging, incus interposition or joint prosthesis use [15]. …”
Section: Discussionmentioning
confidence: 99%
“…The most important result of this (4,10,11). It is considered that the differences among the SBS values of different GICs are due to small variations in their contents.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an inappropriate manipulation may cause stapes to fracture (19). The use of GICs for different ossicular reconstructions such as incus stapes re-bridging, incus augmentation, and the fixation of stapes implants have been shown by several studies as the reliable method (4,12,19,20). Baglam et al reported a significant hearing improvement after incudostapedial rebridging ossiculoplasty with KC (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations